IMPROVING STUDENTS’ WRITING SKILL THROUGH THE USE OF DICTOGLOSS TECHNIQUE “A Study at Nahdlatul Ulama University of NTB” - Ardiansyah, Lalu Dwi Satria (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Abstract This paper is intended to explain the use of the dictogloss technique to improve students’ writing skill at Nahdlatul Ulama University of West Nusa Tenggara. The use of the dictogloss technique for improving students’ writing skill can be represented in each stage of this technique. Moreover, as a technique for language learning, the dictogloss, has preparation stage, dictation stage, reconstruction stage, and analysis-correction stage which facilitate learners in which students work together to reconstruct a dictated-text. They reconstruct the dictated-text by using their own words or in other words they do not write exactly what the lecturer read. Furthermore, the use of the dictogloss technique give a clear advantages for improving students’ writing skill, such as provides an opportunity for learners to use their grammatical knowledge to reconstruct the dictated-text and also encourages learners to find out what they do and do not know about English which is realized in the attempts to reconstruct the text and in the subsequent analysis of those attempts. Besides, the dictogloss technique also contribute to the motivation, learners’ interaction, and grammar in context. Teaching the students grammar in context shows them how to apply various grammatical concepts.